Moral Perceptions of Advised Actions - Coffman, Lucas C.; Gotthard-Real, Alexander (Management Science, 2019)
Can an organization avoid blame for an unpopular action when an adviser advises it to do it? We present experimental evidence suggesting this is the case—advice to be selfish substantially decreases punishment of being selfish. Further, this result is true despite advisers’ misaligned incentives, known to all: Through a relational contract incentive, advisers are motivated to tell the decision makers what they want to hear. Through incentivized elicitations, we find suggestive evidence that advice moves punishment by affecting beliefs of how necessary the selfish action was. In follow-up treatments, however, we show advice does not decrease punishment solely through a beliefs channel. Advice not only changes beliefs about what happened, but also the perceived morality of it. Finally, in treatments in which advisers are available, the data suggest selfish decision makers act more selfishly. This paper was accepted by Axel Ockenfels, behavioral economics.